A história indígena no ensino de História: uma abordagem a partir da Escola Municipal de Ensino Fundamental Francisca Juruna na Reserva Indígena Boa Vista no km 30, Município de Vitória do Xingú - NASCIMENTO, Poliane Silva do (2022)
The teaching of Indigenous History by Law n.11.645 of 2008 has become mandatory in the basic education curriculum throughout the country, so we observe that textbooks still contain many Eurocentric approaches towards indigenous history, especially in the concepts of identity, culture and tradition. In this sense, the objective of this research is to analyze how indigenous people evaluate their active participation in history teaching and how they see themselves through the stories that are portrayed in the classroom. In this work, the following researches were carried out, bibliographical, documentary and field research, where data were collected through interviews with the teacher of the Francisca Juruna school and with the chief of the TI Boa vista km30 of Vitória do Xingu, Juruna community. The results obtained show that the indigenous people want a more representative education, oriented to value the culture and history of the indigenous people, thus seeking improvements in indigenous school education.